TRANSFORMASI E-KTP MENJADI KTP DIGITAL MELALUI APLIKASI IDENTITAS KEPENDUDUKAN DIGITAL (IKD) - Zahro, Aisyah Aulia; Wahyuni, Elli Setiyo (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
The Surabaya City Dukcapil Office has introduced the Digital Population Identity (DPI), an online tool that aims to enhance population administration services by making them more streamlined and efficient. This research aims to assess the utilisation of the DPI Application in promoting efficient population administration in the Bulak Banteng Subdistrict. The research employed a descriptive method with a qualitative approach. The research findings indicate that citizen engagement in utilising the DPI application is manifested through the perceived advantages experienced by residents, such as convenience, time-saving, and the ability to register from anywhere, eliminating the need to visit the office. Consequently, individuals only need to visit Bulak Banteng Subdistrict to collect their prepared documents. Nevertheless, not all individuals opt for services solely through the DPI programme, as there are still inhabitants who remain unaware of the availability of services facilitated by the DPI application. Individuals exhibit a greater level of ease when the service is delivered directly to their workplace, as there is a presumption that utilising the programme will be more challenging. Therefore, this study concludes that the Surabaya City Dukcapil Department's innovation of providing services through the DPI application offers convenience to the community, particularly millennials. However, the implementation of the introduction is suboptimal, and there are instances where the application service is inaccessible to the community, thereby impacting people's willingness to use the DPI application.